Koordinasi Pemerintah dalam Upaya Mitigasi Bencana Banjir di Kecamatan Singkep Kabupaten Lingga : Studi Pada Badan Penanggulangan Bencana Daerah dan Dinas Pekerjaan Umum Tata Ruang - Widia Ierdiana; Rudi Subiyakto; Rizky Octa Putri Charin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Flooding is a natural disaster that still frequently occurs in Singkep District, Lingga Regency, Riau Islands Province. This disaster has quite serious impacts on the community, both in the economic, social, and health sectors. Therefore, the problem of flooding should be a serious concern for the local government, particularly in improving the effectiveness of coordination between agencies directly involved in flood mitigation efforts. This study aims to determine the coordination process between the Regional Disaster Management Agency (BPBD) and the Public Works and Spatial Planning Agency (PUTR) of Lingga Regency in flood management, as well as to identify obstacles encountered in its implementation. The research method used is qualitative with a descriptive approach. The researcher uses the coordination theory of Harold Koontz which emphasizes four important elements: work planning, meetings or interactions, communication, and division of tasks. Data were collected through in-depth interviews, field observations, and documentation from both related agencies. The results of the study indicate that inter-agency coordination has not been running synergistically. The work plans of each agency have not been fully integrated, resulting in the implementation of the flood mitigation program running independently based on their respective duties and functions. The Regional Disaster Management Agency (BPBD) places greater emphasis on non-structural mitigation approaches such as education and simulations, while the Public Works and Housing Agency (PUTR) focuses on technical aspects such as flood control infrastructure development. Inter-agency meetings remain formal and have not yet become collaborative forums for formulating joint policies. Communication and task allocation have occurred, but are limited to the information dissemination stage. Key obstacles to this coordination include budget constraints, a lack of competent personnel, and low public awareness and participation in supporting mitigation programs. The lack of drainage construction in several affected villages also demonstrates weak inter-agency integration in program implementation.